An advanced forwarding routing protocol for urban scenarios in VANETs. Issue 4 (6th November 2017) - Kumar, Sushil; Verma, Anil Kumar
Abstract : Purpose: The purpose of this paper is to give an insight in to the routing protocols in Vehicular ad hoc Network (VANET). In this direction, for the efficient data dissemination in VANETs, a street-based forwarding protocol (SBFP) has been proposed. Design/methodology/approach: The interferences among different street segments are considered and a unique street-based forwarding concept is introduced to reduce the local maximum problem. In this protocol, the greedy forwarding concept along with the broadcasting mechanism and suppression technique is implemented to minimize the overhead created in the regular beacons forwarding processes. QualNet simulator is used to implement and simulate SBFP. SUMO and MOVE tools are used to create the vehicle's movement pattern and network topology. Findings: The simulated results demonstrated improved packet delivery ratio (PDR) with a minimum average number of broadcast by each individual vehicle in the proposed SBFP than in its peer protocols. Originality/value: This paper will be discussing a unique street-based forwarding technique exploring the advantages of global positioning system to obtain the location of vehicles and streets. This technique results in higher PDR and reduced network overhead.